THE MEANING OF DULANG DANCE SYMBOL FOR THE MALAY COMMUNITY ACCORDING TO THE SEMIOTIC THEORY OF FERDINAND DE SAUSSURE - Yusnizar Heniwati; Wiwin Syahputra (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The purpose of this study is to identify the meaning of the Dulang dance symbol based on its function in the Langkat Malay community according to the theory of Ferdinand de Saussure. This research uses qualitative methods with an ethnographic approach. Data collection techniques carried out in this study include observation, interviews and documentation. Researchers as instruments went directly to the field to make engaged or participatory observations to obtain data in the form of detailed descriptive information about the meaning of the Dulang dance symbol in Langkat Regency. Basically, Dulang has a variety of meanings that can be adapted to the function of the Dulang in Malay traditional activities. It can be concluded that the symbolic meaning in this study is that Dulang is a signifier in Dulang dance and other Malay traditional activities. The signified Dulang in Dulang dance and Malay traditional activities include as an expression of gratitude to God Almighty, a symbol of prosperity, and a symbol of strength and power. The existence of Dulang for the Malays, not only as a container or place to place objects or food, but Dulang has a meaning that is able to strengthen the bonds of brotherhood in the Malay community.